2014
DOI: 10.1177/1753193414530591
|View full text |Cite
|
Sign up to set email alerts
|

Splintage in the treatment of sagittal band incompetence and extensor tendon subluxation

Abstract: Level 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Of these, 10 articles were excluded due to inclusion of less than 5 treated digits, 4 were review articles, 4 were descriptions of surgical techniques without any reported patient outcome data, 7 described treatment and outcomes for MCP capsular tears or collateral ligament injuries, and 1 included patients with rheumatoid arthritis. A total of 17 articles were included in the final systematic review and qualitative synthesis 1,3,5,[10][11][12][13][14][15][16][17][18][19][20][21][22][23] (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of these, 10 articles were excluded due to inclusion of less than 5 treated digits, 4 were review articles, 4 were descriptions of surgical techniques without any reported patient outcome data, 7 described treatment and outcomes for MCP capsular tears or collateral ligament injuries, and 1 included patients with rheumatoid arthritis. A total of 17 articles were included in the final systematic review and qualitative synthesis 1,3,5,[10][11][12][13][14][15][16][17][18][19][20][21][22][23] (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Four studies were single-center retrospective case series (Sackett level 4) with the defined inclusion and exclusion criteria, 13,14,17,22 and the remaining 13 were retrospective case reports (Sackett level 4). According to the SEQES scores, only 4 articles were considered to be of moderate quality (scores 17-32), 13,14,17,22 with the remaining being ranked as low-quality articles (scores 0-16). The mean SEQES score was 15 (range, 12-21), with no article achieving a high-quality rating (Figure 2).…”
Section: Study Selection Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Etiologically they are either traumatic or atraumatic. Chronologically Peelman et al 22 classified this pathology based on the time from onset of symptoms into acute (0 to 3 wk), subacute (3 to 6 wk), and chronic ( > 6 wk). Patients with acute injuries to the sagittal band are usually managed with extension splinting to allow primary healing of the extensor mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Recently Peelman et al reported satisfactory results with splintage in the treatment of acute and subacute extensor tendon subluxation due to sagittal band incompetence, with resolution in 95% of all traumatic cases. 64 For closed proximal interphalangeal joint injuries with central slip lesions, a splintage with extended joint for 6 weeks is commonly suggested. A Cochrane revision performed by Chalmer et al observed that there is insufficient evidence from trial testing about the duration and the extent of immobilization of proximal interphalangeal joint after hyperextension trauma.…”
Section: Overviewmentioning
confidence: 99%